2018
DOI: 10.1002/ange.201808929
|View full text |Cite
|
Sign up to set email alerts
|

A Janus Nickel Cobalt Phosphide Catalyst for High‐Efficiency Neutral‐pH Water Splitting

Abstract: Transition-metal phosphides have stimulated great interest as catalysts to drive the hydrogen evolution reaction (HER), but their use as bifunctional catalytic electrodes that enable efficient neutral-pH water splitting has rarely been achieved. Herein, we report the synthesis of ternary Ni 0.1 Co 0.9 P porous nanosheets onto conductive carbon fiber paper that can efficiently and robustly catalyze both the HER and water oxidation in 1m phosphate buffer (PBS;p H7)e lectrolyte under ambient conditions.Awater ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(38 citation statements)
references
References 34 publications
0
38
0
Order By: Relevance
“…b) Polarization curves for overall water splitting consisting of Ni 0.1 Co 0.9 P//Ni 0.1 Co 0.9 P and commercial Pt/C//Ir/C catalysts in 1 m phosphate buffer solution. c) Crystal structure of Ni 0.1 Co 0.9 P. Reproduced with permission . Copyright 2018, John Wiley and Sons.…”
Section: Applicationsmentioning
confidence: 99%
“…b) Polarization curves for overall water splitting consisting of Ni 0.1 Co 0.9 P//Ni 0.1 Co 0.9 P and commercial Pt/C//Ir/C catalysts in 1 m phosphate buffer solution. c) Crystal structure of Ni 0.1 Co 0.9 P. Reproduced with permission . Copyright 2018, John Wiley and Sons.…”
Section: Applicationsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] However, the sluggish kinetic process of OER results in a high overpotential to deliver a desired current density because of its multi-step electron transfer process. [9][10][11][12][13][14] Precious-metal oxides such as IrO 2 and RuO 2 are efficient OER electrocatalysts, but their low abundance and high cost prohibit large-scale applications. [15][16][17] Therefore, the exploration of low-cost electrocatalysts with high OER electrocatalytic activity is highly pursued.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, Wu et al. have attributed the good performance of NiCoP structure to favorable electronic states resulting from the synergistic interplay between nickel and cobalt . Zheng et al have revealed that the adsorption energies of key species can be modulated due to the synergistic effect between Co and Cu in CoCuN catalysts .…”
Section: Resultsmentioning
confidence: 99%